The Attitudes toward Codes of Ethics: Do Cynicism and Religiosity Matters? - Putranta, Martinus Parnawa (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
The prevalence of corporateÂ transgressionsÂ in Indonesia have brought the moral standards of business leaders into public domain. In light of these phenomena, an investigation into whether prospective business leaders of the country are predisposed to moral values is crucial. The purpose of this research was to ascertain the attitudes of the Indonesian future business leaders towards the existence of codes of ethics in business. In particular, the research examined whether the religious orientation of these future leaders influenced the attitudes. A test was also assigned to scrutinize whether the degree of their social cynicism moderated that possible causal relationship. A survey was used as the primary method to collect the data. The sample involved first-year students from a business school at a private university in Indonesia. A total of 111 students involved in the survey. A majority of the students Results of the research showed majority of the respondents were generally supportive shown to have positive attitudes towards codes of ethics. The intrinsic religious orientation of the students also had a positive impact on the attitudes. This positive relationship, however, was mitigated by their negative views of people and social institutions. Managerial implications of the research findings are discussed and the directions of future similar research are outlined.Â